PERSEPSI MAHASISWA ILMU KOMUNIKASI UMY PADA IKLAN TELEVISI ROKOK DJARUM 76 VERSI MENCARI TEMAN HIDUP - Rusman Susanto (IlKom 15 UMY 365, 2015)
*365 Cigarette ads are ads that show a form constrained by banning cigarettes. This is what makes the different cigarette advertising and cigarette advertising agencies need to think more creatively in order to keep advertising for tobacco products. Djarum 76 ads are ads that have different concepts with other cigarette advertising. The focus of this study is a sign of audiovisual perception, namely language, gestures, light, color, text and sound effects. Data collection techniques done is by interview and documentation. This type of research is a descriptive study with qualitative methods. The informants are 3 communication science students who have seen the ad. Results of the study found that the visual appearance of the advertisement Djarum 76 versions look for a life partner consists of signs that give meaning overall audiovisual intact when all the elements are combined. Setting this ad featuring Om Jin said, I gave one request, a woman answered me want to live a good friend, understanding, patient, obedient, loyal and important. With his power, Om Jin also meet that demand, suddenly came the lap of the woman's dog. Om jin was laughing. The conclusion from this study is advertising djarum 76 version to make friends, life is not just promoting the product but also provide social criticism to the problems that are common in the community.